The New Procedure for Identification of Infrastructure Elements Significance in Sub-Sector Railway Transport - Leitner, Bohus; Rehak, David; Kersys, Robertas (Communications - Scientific letters of the University of Zilina, 2018)
The paper focuses on the problem of importance/significance elements evaluation in the railway transport infrastructure sub-systems. It contains main features of the proposed theoretical approach to the significance assessment of the key typological elements of railways infrastructure. The research also attempted to design an effective methodology, which allows assessing the significance of infrastructure objects. The purpose of the multi-criteria assessment of selected sections and typological objects is to select the most significant/important ones from the point of view of maintaining the railway operability. The selection is conducted using the assessment of a section or an object, following the pre-defined criteria. The developed methodology should help to set a group of potential elements of critical infrastructure in the railway sub-sector.